Extraction of healthy oils from fish viscera by conventional and advanced technologies - A. Rohim; T. Estiasih; B. Susilo; F.C. Nisa (Grasas y Aceites, 2024)
Fish viscera is a by-product of fish processing that has limited use as added-value products. The current issue of circular economy to produce recycled and zero waste products, therefore, the utilization of fish viscera for valuable products is important to explore. One of the valuable components of fish viscera is fish oil, which is characterized by being high in polyunsaturated fatty acids (PUFA). The limited exploration of fish viscera for potential utilization requires a comprehensive review of the visceral characteristics of various fish species. This article reviews the nutritional characteristics of various fish viscera, lipid class composition, fish viscera oil characteristics, and various methods of fish viscera oil extraction, both by conventional and advanced technologies. The main contribution of this review is to provide information about fish viscera, their potential as a source of fish oil, and extraction methods which are suitable for various industrial applications and purposes, including health applications for ω-3 fatty acids.